Two-six hours is the optimal timing of intracytoplasmic sperm injection after oocyte pickup: Single-centre 10 years cohort study - Neeta Singh; Neena Malhotra; Reeta Mahey; Garima Patel; Monika Saini (Wolters Kluwer Medknow Publications, 2022)
Background: Optimal incubation period for oocyte competence remains contentious despite intracytoplasmic sperm injection(ICSI) being in practice for 34 years. Dilemma exists as the current literature favors both early and delayed denudation with equivocal results. With ever-rising demand for the procedure this conundrum continues to plague the clinical outcomes. Aims: This study attempts to provide a consensus regarding optimal time duration required for incubating the oocytes after oocyte pickup(OPU) and time to perform ICSI. Settings and Design: A retrospective study in a tertiary centre. Materials and Methods: A retrospective 10-year cohort study including 726 ICSI cycles was conducted in a single tertiary care infertility centre. All cycles comprised at least one metaphase-II oocyte injected with one good quality sperm followed by fresh embryo transfer. The cohort was broadly divided into two groups: (a) Group 1: OPU-ICSI <4 hours(n=466) and (b) Group 2: OPU-ICSI>4 hours(n=260). Statistical Analysis Used: The fertilization(FR) and clinical pregnancy rates(CPR) were compared using the Pearson Chi-square test. The OPU-ICSI interval were subdivided into one-hourly intervals and CPR was compared after adjustment for multiple comparisons by holm method. Results: The FR and CPR were similar between Group 1 and Group 2(p>0.05). Comparing CPR for each one-hourly OPU-ICSI interval revealed no significant clinical difference (p>0.05) amongst one another, however, the CPR was maximum for 2-3 hours as the OPU-ICSI interval. Conclusion: With no significant clinical difference amongst various temporal groups, this study advocates and reinstates 2-6 hours as the optimal timing for ICSI after the OPU. This will also translate into better time management for both embryologists and clinicians and help them prioritise the laboratory workflow.